PROBLEM PADA PASANGAN USIA DINI DI KOTA DENPASAR - Dewi, Yasmin Nirmala; Kebayantini, Ni Luh Nyoman; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
Early marriage in Indonesia is still exists and Denpasar City is no exception as a child-friendly city. Marriage and domestic life of early couples do not run smoothly because they are not ready mentally, socially and economically. Problems in the household cannot be avoided and must be faced by early age couples with planning in forming a family. The purpose of this study was to determine the extent of the obstacles and barriers experienced by early age couples, not only in terms of socio-economics, but also problems in building a household, how to communicate with partners, families and the surrounding community. The method used is descriptive qualitative. The results of this study indicate that early marriage requires various preparations that must be faced by them in their early teens. Not only for responsibility alone, but how to continue married life with the various problems that are in it.